Hepatitis B surface gene variants isolated from blood donors with overt and occult HBV infection in north eastern Egypt. Issue 1 (December 2015) - Kishk, Rania; Nemr, Nader; Elkady, Abeer; Mandour, Mohamed; Aboelmagd, Mohamed; Ramsis, Nevene; Hassan, Mohamed; Soliman, Nashaat; Iijima, Sayuki; Murakami, Shuko; Tanaka, Yasuhito; Ragheb, Mostafa
Abstract Background Major hydrophilic region in genomic HBV extending from aa99 to aa169, clustered with a highly conformational epitope, is critical to the antigenicity of hepatitis B surface antigen (HBsAg) and may affect the diagnosis of HBV in HBV screening test. So, this study aimed to characterize variants of S gene product of hepatitis B virus (HBV) isolated from patients with overt or occult HBV infection in north-eastern Egypt. Methods The study included sera of two different groups of volunteer blood donors (VBDs), 82 with overt HBV that were positive for HBsAg and anti-HBc and 343 donors negative for HBsAg eligible for donation. Of the latter group, only 44 were positive for anti-HBc. All anti-HBc positive sera were subjected to HBV DNA detection and partial sequence analysis targeting the HBV S gene. Results HBV DNA was detected in 22.7 % of HBsAg-/anti-HBc + (10/44 patients) and in 90 % of HBsAg + donors (74/82 patients) with significant statistical difference (P = 0.0001). Phylogenetic analysis showed that HBV strains retrieved from both groups were of genotype D. Amino acid escape mutation T125M was detected in only 2 samples of the occult infection group and in none of the overt group (P = 0.01). Different amino acid substitutions were identified in overt infection group: S143L/T (16.2 %, 12/74) and P120T/S (2.7 %, 2/74). Q129R was significantly more frequent in cases with occult HBV infection (40 %, 4/10) than overt group (6.8 %, 5/74) (P = 0.01). Conclusions HBV genotype D predominated both in patients with overt and occult HBV infection. Different profiles of amino acid substitutions in the major hydrophilic region were seen in these two groups in Egypt.